Pharmaceutical Applications of the Benzylisoquinoline Alkaloids from Argemone mexicana L. - Rubio-Pina, Jorge; Vazquez-Flota, Felipe (Current Topics in Medicinal Chemistry, 2013)
Argemone mexicana L. (Papaveraceae), accumulates benzylisoquinoline alkaloids, (BIA) derived from tyrosine. Although it was originated in the western region of the USA-Mexico border, it has spread to tropical and subtropical areas around the world. Today, it is used to treat different ailments, given to its antimicrobial, antiparasitic, antimalarial, pesticide, cytotoxic and neurological properties. These effects are related to the presence of different types of BIA’s, such as benzophenanthridines (sanguinarine, chelerythrine), protoberberines (berberine) and protopines (protopine, allocryptopine). This review covers the historical medicinal uses of A. mexicana, as well as its current applications. The chemical bases of such effects are discussed in relation to the occurrence of the different types of alkaloids. The biochemical process involved in the synthesis of these types of alkaloids is also described.
Keywords: Argemone mexicana